Robot Lawyer in Indonesian Criminal Justice System: Problems and Challenges for Future Law Enforcement - Fernando, Zico Junius; Kristanto, Kiki; Anditya, Ariesta Wibisono; Hartati, Sawitri Yuli; Baskara, Agri (Universitas Negeri Semarang, 2023)
The rapid advancement of artificial intelligence (AI) introduces unprecedented opportunities and complexities, particularly in its intersection with the legal domain. This study envisions a future where autonomous decision-making robot lawyers play a pivotal role in legal proceedings, providing counsel and representation. Examining the implications of AI’s scientific progress on Indonesian law, normative legal research methods were employed, encompassing statutory, conceptual, comparative, and futuristic analyses. Qualitative scrutiny and content analysis were applied to collected materials. The study reveals the potential of robot lawyers to enhance efficiency in Indonesia’s criminal justice system, aiding in evidence gathering, case analysis, and indictment drafting. This technological integration promises to alleviate the workload of legal professionals and expedite case resolutions, thereby improving public access to legal services. However, challenges loom, including ethical concerns, data security, and professional qualifications. To address these challenges, the study advocates for collaborative efforts among the government, industry, and academia. This cooperation is crucial for formulating regulations and establishing supportive infrastructure for the seamless integration of robot lawyers. Additionally, enhancing digital literacy and public understanding of AI in the legal sphere is emphasized as a vital step toward maximizing the benefits of this technology. In essence, the study underscores the transformative potential of AI in reshaping legal processes, emphasizing the need for a concerted, informed effort to navigate the challenges and optimize the benefits of this evolving technological landscape.